Penentuan Efektifitas Oksitetrasiklin Melalui Parameter Farmakokinetik/farmakodinamik pada Plasma dan Jaringan Ayam Broiler - Dwi Wijayanti, Agustina; Hakim, Lukman; Widiyono, Irkham; Irianti, Tatang (Jurnal Veteriner, 2010)
A study was conducted to determine the effectiveness of oxytetracycline on the basis of itspharmacokinetic/pharmacodynamic (PK/PD) parameters in the plasma and tissues of broiler following a50 mg/kg single dose of intravenous administration. The male broiler were injected with oxytetracycline attarsal medial venous. The blood, liver, kidney and abdominal muscle were collected at 14 points of timesamplings. Blood was centrifuged to obtain plasma and all tissues were extracted with Mc Ilvine buffer.Drug concentration in samples was determined by High Performance Liquid Chromatography (HPLC)using AOAC standard reference for tetracycline. The pharmacokinetic parameters of oxytetracycline werecalculated using non compartment method. The results were as follows. For plasma: the AUC was 790,615,5 ?g/mL minute , Clearance was 63,242 mL/min/kg bb, Tmax/Cmax was 1 minute/0,7 ?g/mL, T1/2elimination was 6,4, hours, Vd was 37 L/kg. For liver ; AUC was 36418,89, minute , Tmax/Cmax was 16hours/17,15 ?g/g, and T1/2 elimination was 24,5, hours. For kidney; AUC6808,41 ?g/g minute , Tmax/Cmax 1 minute/16,73 ?g/g, , T1/2 elimination was 11,55 hours. For muscle; AUC was 3502 ?g/g minute,Tmax/Cmax was 1 minute/2,58 ?g/g, T1/2 elimination was 167,39 hours. The ratio of AUC/MIC inplasma and tissues appeared to a good pharmacokinetic/pharmacodynamic parameter to determine theeffectiveness of oxytetracycline.
Keywords: pharmacokinetic, oxytetracycline, PK/PD parameter, broiler